PERTUMBUHAN EKONOMI, KESEMPATAN KERJA, KEMISKINAN DAN KETIMPANGAN PENDAPATAN DI PROVINSI JAMBI - Idris, Kamal; Syaparuddin, Syaparuddin; Hodijah, Siti (Jurnal Paradigma Ekonomika, 2014)
Economic Growth, Work Opportunity, Poverty and Income Inequality in Regencies of Jambi, like: Sarolangun, Muaro Jambi, Tanjung Jabung Barat and Bungo. This thesis aims to (1) Indentify and analize economic growth, work opportunity, poverty and income inequality (2) determine and analyze economic growth influence towards work opportunity, poverty and income inequality in Merangin, Sarolangun, Muaro Jambi, Tanjung Jabung Barat and Bungo in Regencies of Jambi. This research use quantitative analyze, procesed using Eviews4 Program. The result of this research show that the average of economic growth in Sarolangun and Bungo is higher than economic growt in Jambi. The other side, the average of economic growth in Merangin, Muaro Jambi and Tanjung Jabung Barat lower than the average of economic growth in Jambi. Eonomic Growth has positive good influence towards work opportunity and has negative influence towards income inequality in Merangin, Sarolangun, Muaro Jambi, Tanjung Jabung Barat and Bungo in Regencies of Jambi. Keywords : Economic Growth, Work Opportunity, Poverty, and Income Inequality.